An Ultrahigh‐Flux Nanoporous Graphene Membrane for Sustainable Seawater Desalination using Low‐Grade Heat. Issue 11 (3rd February 2022) - Lu, Dongwei; Zhou, Zongyao; Wang, Zhihong; Ho, Duc Tam; Sheng, Guan; Chen, Long; Zhao, Yumeng; Li, Xiang; Cao, Li; Schwingenschlögl, Udo; Ma, Jun; Lai, Zhiping
Abstract: Membrane distillation has attracted great attention in the development of sustainable desalination and zero‐discharge processes because of its possibility of recovering 100% water and the potential for integration with low‐grade heat, such as solar energy. However, the conventional membrane structures and materials afford limited flux thus obstructing its practical application. Here, ultrathin nanoporous graphene membranes are reported by selectively forming thin graphene layers on the top edges of a highly porous anodic alumina oxide support, which creates short and fast transport pathways for water vapor but not liquid. The process avoids the challenging pore‐generation and substrate‐transfer processes required to prepare regular graphene membranes. In the direct‐contact membrane distillation mode under a mild temperature pair of 65/25 °C, the nanoporous graphene membranes show an average water flux of 421.7 L m −2 h −1 with over 99.8% salt rejection, which is an order of magnitude higher than any reported polymeric membranes. The mechanism for high water flux is revealed by detailed characterizations and theoretical modeling. Outdoor field tests using water from the Red Sea heated under direct sunlight radiation show that the membranes have an average water flux of 86.3 L m −2 h −1 from 8 am to 8 pm, showing a great potential for real applications in seawater desalination. Abstract : An ultrathin nanoporous graphene membrane is developed, which creates short and fast transport pathways for water vapor but not liquid. The fabrication process avoids the challenging pore‐generation and substrate‐transfer processes generally required for graphene membranes. In direct‐contact membrane distillation mode under a mild temperature gradient, the membrane shows outstanding performance and holds great potential for water desalination toward a low‐carbon future.